Contextualising measures of everyday discrimination experienced by Aboriginal peoples: A place-based analysis from central Australia. (December 2022) - Wright, Alyson; Davis, Vanessa Napaltjarri; Bourke, Sarah; Lovett, Raymond; Foster, Denise; Klerck, Michael; Yap, Mandy; Richardson, Alice; Sanders, William; Banks, Emily
Abstract: Everyday discrimination is a deeply personal experience, which is influenced by the wider community, as well as complex social and historical contexts. In Australia, the most recent national data for Aboriginal and Torres Strait Islander peoples reports the highest prevalence of everyday discrimination among those living in remote regions compared with urban and regional areas. Given the diversity in settlement types in remote Australia, a place-based analysis can inform the extent of discrimination experienced and the impact on communities. This study used a mixed method approach to identify Indigenous community member understandings of discrimination and quantify everyday discrimination in Central Australia by settlement. Drawing on workshop data from community members, we defined two research questions: Do experiences of everyday discrimination vary according to where people live? What role does community cohesion have on experiences of discrimination? We used data from the Mayi Kuwayu Study to explore these questions. The studyfound a high prevalence of everyday discrimination, with 70.6% (n/N = 369/523) of Mayi Kuwayu participants in Central Australia experiencing any discrimination which triangulated with people's experience of overt racism. Discrimination varied by settlement type, with higher prevalence of experiencing any discrimination among participants in Town Camps (unadjusted PR 1.33, 95%CI 1.18–1.50) and suburbs (1.19, 1.05–1.35) compared to participants from remote communities. High community cohesion attenuates the prevalence of the discrimination (0.87, 0.77–0.97). If health and social outcomes are to improve among Aboriginal people in remote areas, societal responses must acknowledge the high prevalence of discrimination in places where race and social inequalities are stark, act to confront interpersonal and systemic prejudices, and build cohesive communities. Highlights: Indigenous make up 3.3% of Australian population, but are 45% of the remote population. Experiences of everyday discrimination for Aboriginal and Torres Strait Islander peoples are highest in remote areas in Australia. A place-based analysis of Central Australia shows everyday discrimination is most prevalent among people living in town rather than remote communities. Strong community cohesion attenuates experiences of everyday discrimination and is an important strategy for Town Camps and remote communities.